Microbiology of acute otitis externa - Roland, Peter S; Stroman, David W (The Laryngoscope, 2002)
To isolate and characterize bacteria and fungi from acute otitis externa (AOE) and to obtain susceptibility profiles on each bacterial isolate. Prospective core series. Specimens were collected from the external canals of subjects with clinically diagnosed acute otitis externa. Species-level identification for each bacterial isolate recovered was obtained by combining phenotypic and genotypic data. End point mean inhibitory concentration (MIC) testing was performed using National Committee for Clinical Laboratory Standards (NCCLS) recommended methods. In Alcon-sponsored clinical studies conducted in 1998 to 2000, microbiology specimens were collected from 2039 subjects (2240 diseased ears) by 101 investigators throughout the United States. A total of 2838 bacteria, 32 yeast, and 17 molds were recovered from 2048 ears clinically diagnosed as acute otitis externa. Of the 202 bacterial species recovered, the species most frequently isolated was Pseudomonas aeruginosa (38%). The next 10 species most frequently isolated were: Staphylococcus epidermidis, 9.1%; Staphylococcus aureus, 7.8%; Microbacterium otitidis, 6.6%; Microbacterium alconae, 2.9%; Staphylococcus caprae, 2.6%; Staphylococcus auricularis, 2.0%; Enterococcus faecalis, 1.9%; Enterobacter cloacae, 1.6%; Staphylococcus capitis subsp. Ureolyticus,1.4%; and Staphylococcus haemolyticus, 1.3%. Susceptibility profiles of S. epidermidis isolates revealed the greatest frequency of high-level resistance to selected antibiotics (>/=8 microg/mL): 23%, neomycin-resistant; 11%, oxacillin-resistant; and 12%, ofloxacin-resistant. Susceptibility profiles of S. aureus isolates revealed a lower frequency of high-level resistance: 6.3%, neomycin-resistant; 2.7%, oxacillin-resistant; and 4.5%, ofloxacin-resistant. P. aeruginosa with high-level resistance to quinolones (>/=128 mcg/mL for ofloxacin) was recovered from only 1 subject. Likewise, resistance of P. aeruginosa to aminoglycosides was rare. Twenty isolates had neomycin MICs >/=64 mcg/mL and 10 isolates had gentamicin MICs >/=16 mcg/mL. The coryneform isolates identified as Microbacterium otitidis had an intrinsic lack of susceptibility to quinolones (ofloxacin MICs >/=16 mcg/mL) and aminoglycosides (tobramycin MICs >/=32 mcg/mL and gentamicin MICs >/=8 mcg/mL). Bacterial infections of the external ear canal are most often caused by P. aeruginosa. However, there are a great number of other gram-positive and gram-negative bacterial species that are recovered from patients with acute otitis externa. Because of this diverse etiology, the best topical therapeutic choice for topical therapy is for the most potent, broad-spectrum (especially anti-P. aeruginosa) antibiotic available.